Metaverse forensics: a preliminary analysis of opportunities and challenges - Kamoun, Faouzi (Forecasting cyber crimes in the age of the metaverse, 2024)
The metaverse is poised to offer an immersive virtual environment for people to meet, socialize, collaborate, play, and conduct business transactions. Although the metaverse has not yet reached its full maturity, it has already been misused to launch illegal activities that can jeopardize the safety and well-being of individuals, and cause harm to organizations. Despite its increased importance, “metaverse forensics” remains an unexplored research topic. This chapter starts by reviewing the state-of-the-art research related to metaverse cybersecurity threats and underlying ethical, privacy, and legal issues. It then presents the results of a forensic investigation analysis performed on the VRChat and AltspaceVR metaverse platforms. The authors present new insights into metaverse forensics in terms of accessing digital containers and retrieving useful information for forensic investigators. Additionally, they highlight the primary obstacles encountered in metaverse digital forensic investigations and put forth recommendations for future research directions.